COMPLETE CONVERGENCES AND STRONG LAWS OF LARGE NUMBERS FOR WEIGHTED SUMS PAIRWISE NQD RANDOM VARIABLES SEQUENCE - Cai, Guang- hui (Journal of the Indonesian Mathematical Society, 2007)
"PDF FILE"DOI :Â http://dx.doi.org/10.22342/jims.13.1.89.91-98